Peran Baznas Dalam Aktivitas Perputaran Ekonomi di Kota Palembang: Studi Tingkat Kesadaran Masyarakat Terhadap Tanggung Jawab Membayar Zakat Periode Tahun 2020 – 2025 - Maharani Azizah; Wahyu Sarvian Putra; Rissa Azzahra; Maya Panorama (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
Indonesia is one of the countries with the largest Muslim population, with 87.2% of its citizens adhering to Islam. This makes Indonesia the country with the greatest zakat potential in the world, where zakat can be utilized as one of the instruments of national revenue and play a significant role in poverty alleviation and improving public welfare. The types of data used in this research include both primary and secondary data. This study aims to analyze the level of zakat in Palembang City, the impact of zakat on the local economic circulation during the period 2020–2025, and the optimization of zakat funds for the welfare of the community. The results of this study indicate that the level of public awareness in Palembang City is at 4.38, which means that the community understands the obligation of paying zakat. However, public trust in zakat management institutions remains questionable, particularly regarding financial transparency.